Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-05-12T16:07:44+02:00

3x-7=-2x-9

3x-7+2x=-2x-9+2x

5x-7=-9

5x-7+7=-9+7

5x=-2

x=-2/5

x=-0.4

 

3x-2+x=6+4x

4x-2=6+4x

4x-2-4x=6

x-2=6

x-2+2=6+2

x=8

 

4-5x=9x

4-5x-9x=9x-9x

4-14x=0

4-14x-4=0-4

-14x=-4

x=-4/-14

 

voilà..... :)

 

2013-05-12T16:43:04+02:00

3x - 7 = - 2x -9  ALORS                         3x - 2+x = 6+ 4x

3x+2x = -9 +7                                           3x-3x = 6 +4x

5x= -2                                                        3x-3x -4x = 6

x = -2%5 ALORS                                        -4x= 6    ALORS  x= 6% -4  = -1,5       x= -1,5

 x=0,4 

 

    

 

4-5x= 9x            

 

4=9x+5x   

 

4=14x      ALORS x = 14%4 = 3,5                DONC  x = 3,5